2008
DOI: 10.1021/jf800972m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultra-High-Pressure Homogenization Treatment on the Lipolysis and Lipid Oxidation of Milk during Refrigerated Storage

Abstract: Free fatty acid (FFA) release and quantification and lipid oxidation extent of ultra-high-pressure homogenized (UHPH) milk samples were evaluated to assess the effect of UHPH on the susceptibility of milk lipids to lipolysis and oxidation. Milk was UHPH-treated at 200 and 300 MPa with inlet temperatures of 30 and 40 degrees C. UHPH-treated samples were compared to high-pasteurized milk (PA; 90 degrees C, 15 s). Results showed that all FFA increased significantly during storage only in 200 MPa samples. Lipid ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 27 publications
9
32
0
Order By: Relevance
“…HPH did not influence either the fatty acid composition or the free acidity of EYC, in agreement with Pereda et al [22] and Rodriguez et al [23]. The decreased free acidity observed in EYC containing the highest NaCl concentration could be accounted to changes in lipase activity, already reported in flours having 1% NaCl concentration [24].…”
Section: Open Access Fnssupporting
confidence: 89%
“…HPH did not influence either the fatty acid composition or the free acidity of EYC, in agreement with Pereda et al [22] and Rodriguez et al [23]. The decreased free acidity observed in EYC containing the highest NaCl concentration could be accounted to changes in lipase activity, already reported in flours having 1% NaCl concentration [24].…”
Section: Open Access Fnssupporting
confidence: 89%
“…A similar phenomenon was reported by Pereda, Ferragut, Quevedo, Guamis, and Trujillo (2008), who confirmed that 300 MPa treatments resulted in higher TBARS values compared with 200 MPa treatments. Cava, Ladero, Gonz alez, Carrasco, and Ramírez (2009) found that in dry-cured ham and loins, the TBA values significantly increased, even at lower pressure (200 and 300 MPa), regardless of the time of treatment.…”
Section: Antioxidant Activity Epa Dha and Tbarssupporting
confidence: 87%
“…On the other hand, oleic acid, decreased the least (Table 7). Pereda et al (2008) found no statistically significant differences in the content of FFA in pasteurized milk during a 7-day storage, although the quantity of these acids decreased slightly. L orenzen et al (2011) reported that micro-filtered ESL milk exhibits a lower heat load than ESL heated at a high temperature (pasteurized), resulting in an increase in residual lipase activity, which may accelerate the generation of FFA during prolonged storage.…”
Section: Whey Proteinsmentioning
confidence: 60%